A Dynamic Network Approach to the Study of Syntax - Diessel, Holger (Frontiers in Psychology, 2020)
Usage-based linguists and psychologists have produced a large body of empirical results suggesting that linguistic structure is derived from language use. However, while researchers agree that these results characterize grammar as an emergent phenomenon, there is no consensus among usage-based scholars as to how the various results can be explained and integrated into an explicit theory or model. Building on network theory, the current paper outlines a structured network approach to the study of grammar in which the core concepts of syntax are analyzed by a set of relations that specify associations between different aspects of a speaker’s linguistic knowledge. These associations are shaped by domain-general processes of language use that can give rise to new structures and meanings in language acquisition and language change. Drawing on research from both linguistics and psychology, the paper proposes specific network analyses for the following phenomena: argument structure, word classes, phrase structure, constructions and construction families, and grammatical categories such as voice, case and number.